Virtual Lab Development to Support Automotive Electrical Practicum Course - Dani Irawan; Erwin Komara Mindarta; Sumarli Sumarli; Citra Kurniawan (Universitas Sultan Ageng Tirtayasa, 2022)
Throughout 2020, what was implemented at UM had an impact on the learning of practical subjects. Practical learning that has been carried out in laboratories/workshops must switch to an online system. One of them is the Body Electrical Practicum course, 3 credits/6 JS. Due to the nature of courses that are usually carried out by laboratories to provide effective skill acquisition and hands-on experience, it is often difficult to make these laboratories accessible online. Therefore, the solution offered in this research is to develop virtual lab-based learning content to complement the learning content that has been implemented so far. The purpose of this research is (1) to produce appropriate learning media (2) to test the effectiveness of the developed media. This research method uses research and development of the ADDIE model which consists of analysis, design, development, and implementation. Meanwhile, the data analysis used is in the form of a percentage that describes the size of the feasibility of the virtual lab developed according to experts, and the tow tail test is used to test the effectiveness. Based on the feasibility test from the experts that the developed media is suitable for learning in electrical courses in the Department of Mechanical Engineering, State University of Malang with minor revisions. While the results of the effectiveness test show that the media developed is very effective, as evidenced by an increase in the value of the respondents who are the object of the test. The contribution of this research is to complement the offline practical learning that has been carried out so far, so that it can provide solutions for online practicum models during the pandemic.